Taxonomic revision of the genus Atmetonychus (Coleoptera: Curculionidae: Entiminae) from the Indian subcontinent - G. Mahendiran; V. V. Ramamurthy (Journal of Threatened Taxa, 2017)
Genus Atmetonychus Schoenherr (1840) known from India and Bangladesh is revised.  The generic and species description has been updated through addition of measurements, description of elytral vestiture and genitalic characters. These are supported by 28 illustrations including 21 line diagrams.